Els futurs mestres i el procés de normalització lingüística. Relacions entre els factors familiars, socials i educatius en la formació de la competència i l'actitud lingüístiques - Baldaquí, Josep Maria; Cano, M. Antònia (Caplletra. Revista Internacional de Filologia, 1996)
School is one of the basic pillars of the linguistic normalization process, and teachers play a fundamental role in encouraging this task. Therefore, teacher training, and more particularly its first stages, is a basic area of analysis. It is of great interest to study Teacher Training College students, the teachers of a not so distant tomorrow, regarding their knowledge and use of the language, their linguistic attitudes and rules of usage and, most specifically, their expectations concerning professional use of Catalan. This paper analyzes these issues from the point of view of the Alacant province area, by showing the surveys carried out during the academic years 1993-94, 1994-95 and 1995-96 among the students of the Escola Universitària de Formació del Professorat (Teacher Training College) at the University of Alacant. An analysis of the results, which is moderately optimistic, points out a few structural faults in the Valencian educational system and proposes a number of priority measures.